2015
DOI: 10.1097/cej.0000000000000080
|View full text |Cite
|
Sign up to set email alerts
|

Association between socioeconomic and demographic characteristics and utilization of colonoscopy in the EPIC–Heidelberg cohort

Abstract: We aimed to describe the utilization of colonoscopy and its association with sociodemographic characteristics within the European Prospective Investigation into Cancer and Nutrition (EPIC)-Heidelberg cohort study. We included 15 014 study participants (43% men) of the EPIC-Heidelberg cohort recruited between 1994 and 1998. At baseline recruitment, as well as in the 3-yearly follow-up surveys, study participants completed questionnaires on lifestyle, socioeconomic background variables, health status, and use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
(22 reference statements)
2
3
0
Order By: Relevance
“…In our study, there were no relevant differences in colonoscopy use according to estimates of SES defined by educational level. This is consistent with the results of the analyses by Hermann et al (2015 ) including 15 014 participants aged 35–60 years of the EPIC study in Germany where no association with educational but a weak positive association with vocational training was observed. In a study by Sieverding et al (2010 ), also no clear association was found between education and colonoscopy use in Germany in both sexes.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, there were no relevant differences in colonoscopy use according to estimates of SES defined by educational level. This is consistent with the results of the analyses by Hermann et al (2015 ) including 15 014 participants aged 35–60 years of the EPIC study in Germany where no association with educational but a weak positive association with vocational training was observed. In a study by Sieverding et al (2010 ), also no clear association was found between education and colonoscopy use in Germany in both sexes.…”
Section: Discussionsupporting
confidence: 91%
“…Further models included addi-tional covariates, the 10-year risk for cardiovascular disease, and the family history of CRC (model-2) and age, sex, presence of metabolic syndrome, smoking status, family history of CRC, red meat consumption, and physical activity (model-3). Odds ratios (OR) and respective 95% confidence intervals (CI) were calculated for the binary depend- [21,22]. In line with these preliminary studies, the average age of patients with low education status was also higher in our study, indicating that these patients came for screening later in their life.…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, in our study, the participants with lower education reported even less physical activity, whereas the amounts of red meat as main meal were different statistically, but this difference did not seem clinically relevant. There is also evidence that patients with lower education are less likely to participate in CRC screening [ 21 , 22 ]. In line with these preliminary studies, the average age of patients with low education status was also higher in our study, indicating that these patients came for screening later in their life.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from observed AN risk among those who participate in screening colonoscopy, sex‐specific differences are also expected with respect to socioeconomic status (SES) and use of screening colonoscopy, with stronger associations between SES and colonoscopy screening participation among males than females 29 . If consideration of SES may increase the explainable proportion of male excess risk should be investigated in further studies.…”
Section: Discussionmentioning
confidence: 99%